2001
DOI: 10.1056/nejm200105243442101
|View full text |Cite|
|
Sign up to set email alerts
|

Maternal and Fetal Outcomes of Subsequent Pregnancies in Women with Peripartum Cardiomyopathy

Abstract: Subsequent pregnancy in women with a history of peripartum cardiomyopathy is associated with a significant decrease in left ventricular function and can result in clinical deterioration and even death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
207
1
12

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 451 publications
(227 citation statements)
references
References 10 publications
5
207
1
12
Order By: Relevance
“…The risk of poor outcome of subsequent pregnancy is high in patients with incomplete left ventricular recovery. Even in patients with recovered left ventricular function, there is an increased risk of complications including recurrent HF and reduced LVEF with subsequent pregnancy (118,119).…”
Section: Prognosismentioning
confidence: 99%
“…The risk of poor outcome of subsequent pregnancy is high in patients with incomplete left ventricular recovery. Even in patients with recovered left ventricular function, there is an increased risk of complications including recurrent HF and reduced LVEF with subsequent pregnancy (118,119).…”
Section: Prognosismentioning
confidence: 99%
“…18 Elkayam et al reported that subsequent pregnancies in patients with peripartum cardiomyopathy were associated with significant decrease in left ventricular function and functional status. 19 Fifty percent of the women who were followed up at our institution were still symptomatic at six months postpartum.…”
Section: Discussionmentioning
confidence: 93%
“…30 Approximately 75% of cases are diagnosed within the first month postpartum and 45% present in the first week after birth. 31 The incidence of PPCM in the United States is difficult to estimate as the diagnosis overlaps with other cardiomyopathies. The highest incidence of PPCM occurs in African American women compared to other racial groups.…”
Section: Pregnancy and Peripartum Cardiomyopathymentioning
confidence: 99%
“…Eventual recovery of left ventricular systolic function occurred more frequently in women who had an EF of >30% at original diagnosis of PPCM. 31 However, the safety of subsequent pregnancies remains a concern. Elkayam et al report that women with PPCM exhibit a significant decline in left ventricular function with subsequent pregnancies.…”
Section: Pregnancy and Peripartum Cardiomyopathymentioning
confidence: 99%
See 1 more Smart Citation